2018
DOI: 10.1136/bcr-2018-224236
|View full text |Cite
|
Sign up to set email alerts
|

Acute hepatitis E infection as a cause of unexplained neurological symptoms

Abstract: Neurological disease is the most common extrahepatic manifestation of autochthonous infection with hepatitis E virus (HEV). The association between acute neurological symptoms and hepatitis E is not well known, and hence HEV testing is often omitted. This case describes aberrant neurology in a 35-year-old woman with a background of HEV infection, highlighting the need for increased awareness of acute hepatitis E infection as a cause of unexplained neurological illness.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
3
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 20 publications
(18 reference statements)
0
3
0
Order By: Relevance
“…The other rarer neurological manifestations that were reported include mononeuritis multiplex [10], encephalitis [11,13,39,41], cerebral ischemia [11,39], myasthenia gravis [42], polyneuromyopathy [24,43], meningo-radiculitis [10,44], epilepsy [11], encephalopathy [45], facial nerve palsy [11,46,47], encephalitic parkinsonism [48], transverse myelitis [49], peripheral neuropathy [24,39,50], vestibular neuritis [24], small fiber neuropathy [24], Myositis [51], and certain non-specific neurological symptoms like myalgias, joint pains, etc. [52,53] which are summarized in Table 1. CR: case report; RS: retrospective study; CC: Case-Control study; CS: Case Series; CSS: cross-sectional study; * one patient each was reported to have Miller-Fiser variant of Guillain-Barré syndrome; # report of a patient with anterior interosseous mono-neuropathy.…”
Section: Neurological and Musculoskeletal Manifestationsmentioning
confidence: 99%
“…The other rarer neurological manifestations that were reported include mononeuritis multiplex [10], encephalitis [11,13,39,41], cerebral ischemia [11,39], myasthenia gravis [42], polyneuromyopathy [24,43], meningo-radiculitis [10,44], epilepsy [11], encephalopathy [45], facial nerve palsy [11,46,47], encephalitic parkinsonism [48], transverse myelitis [49], peripheral neuropathy [24,39,50], vestibular neuritis [24], small fiber neuropathy [24], Myositis [51], and certain non-specific neurological symptoms like myalgias, joint pains, etc. [52,53] which are summarized in Table 1. CR: case report; RS: retrospective study; CC: Case-Control study; CS: Case Series; CSS: cross-sectional study; * one patient each was reported to have Miller-Fiser variant of Guillain-Barré syndrome; # report of a patient with anterior interosseous mono-neuropathy.…”
Section: Neurological and Musculoskeletal Manifestationsmentioning
confidence: 99%
“…Furthermore, it is believed that regional differences in clinical presentation as well as genotypes are relevant and should be considered when diagnosing neurological manifestations of HEV [ 26 ]. Due to the great heterogeneity of clinical phenotypes and the largely unknown pathomechanism, it is important to consider HEV in unusual neurological cases [ 27 ] in addition to the most common neurological manifestations GBS and neuralgic amyotrophy [ 6 8 , 12 , 16 , 21 , 28 ].…”
Section: Discussionmentioning
confidence: 99%
“…1 Treatment is usually supportive, although ribavirin has been used in severe illness or in the immunosuppressed 9 who may experience chronic infection. 10 The commonest reported extrahepatic manifestations reported are neurological, occurring in 7.5% of individuals with acute hepatitis E. 11 Rash has been reported in around 3% in some European series 12,13 and cryoglobulinaemia has also been reported. 14 We note one similar case report in the Lancet in 2013, describing a woman presenting with a widespread, maculopapular rash and transaminitis.…”
Section: Discussionmentioning
confidence: 99%